ANALISIS KETEPATAN KODIFIKASI DIAGNOSA ICD-10 GUNA MENUNJANG EFEKTIVITAS PENGKLAIMAN PASIEN BPJS RAWAT JALAN - Rita Sulistiawati (Jurnal Infokes, 2023)
This study aims to determine the description of the implementation, problems, and any efforts regarding the codification of ICD-10 diagnoses to support the effectiveness of outpatient BPJS patient claims at Muhammadiyah Hospital Bandung. The research method used is a qualitative research method with a descriptive approach, while data collection is done through literature study, interviews and observations. From the research that has been carried out, there are several problems found, namely empty diagnoses or nor filled in by the doctor on the medical resume, unreadable diagnostic writing, the existence of diagnostic abbrevations that are not understood, the file that will be claimed is returned by BPJS to the Hospital. The suggestions given for this problem are, nurse remind doctors to always make sure outpatient medical resumses are filled out completely, socialization was held between the coder and the doctor, so that the writing of final diagnostic code on the medical resume can be understandable, a meeting was held between the coder and the doctor, for evaluation and discussion of which diagnoses were given abbreviation, before the file to be claimed is sent, it is better for the verifier officier to chrosscheck it first. Keyword : Codification, Effectiveness, BPJS Claims